Conformational Distributions and Hydrogen Bonding in Gel and Frozen Lipid Bilayers: A High Frequency Spin-Label ESR Study - Dzikovski, Boris (2012)
The ESR parameters of PC spin labels in frozen membranes do not simply represent the membrane polarity or water penetration profile. Instead, they show a distribution between hydrogen-bonded (HB) and non-hydrogen bonded (non-HB) states, which is affected by a number of factors in the membrane composition. Similar to the exclusion of solutes from crystallizing solvents, the pure bulk gel phase excludes nitroxides, forcing acyl chains to take bent conformations. In these conformations the nitroxide is hydrogen-bonded. Furthermore, upon gradual cooling in the supercooled gel PC labels undergo slow lateral aggregation resulting in a broad background signal. However, if the sample is instantly frozen, this background is replaced by the HB component. In membranes with cholesterol the observed HB/ non-HB ratio can best be described by a partition-like equilibrium between nitroxides located in defects of lipid structure within the hydrophobic core and those close to the membrane surface.